Role of Manganese-Containing Superoxide Dismutase in Oxidative Stress and Virulence of Streptococcus pneumoniae - Yesilkaya, Hasan (American Society for Microbiology, 2000)
Streptococcus pneumoniae was shown to contain two types of superoxide dismutase, MnSOD and FeSOD. Levels of MnSOD increased during growth in an aerobic environment. The sodA gene, encoding MnSOD, of virulent S. pneumoniae type 2 strain D39 was inactivated to give mutant D39HY1. Aerobically, D39HY1 had a lower growth rate than the wild type and exhibited susceptibility to the redox-active compound paraquat, but anaerobic growth of D39HY1 was identical to that of the wild type. Virulence studies showed that the median survival time of mice infected intranasally with D39HY1 was significantly longer than that of mice infected with the wild-type pneumococcus. In contrast to the wild type, D39HY1 did not multiply in lungs during the first 24 h but thereafter grew at the same rate as the wild type. Appearance in the bloodstream was also delayed, but growth in the blood was unimpaired by the sodA mutation. The pattern of inflammation in lungs infected with D39HY1 differed from that in wild-type-infected mice. After infection with D39HY1, neutrophils were densely packed around bronchioles, in contrast to the wild-type infection, where neutrophils were more diffusely localized.